2016
DOI: 10.4103/0973-1296.182160
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis and comparison of four major flavonol glycosides in the leaves of Toona sinensis (A. Juss.) roemer (chinese toon) from various origins by high-performance liquid chromatography-diode array detector and hierarchical clustering analysis

Abstract: Background:Toona sinensis (A. Juss.) Roemer is an endemic species of Toona genus native to Asian area. Its dried leaves are applied in the treatment of many diseases; however, few investigations have been reported for the quantitative analysis and comparison of major bioactive flavonol glycosides in the leaves harvested from various origins.Objective:To quantitatively analyze four major flavonol glycosides including rutinoside, quercetin-3-O-β-D-glucoside, quercetin-3-O-α-L-rhamnoside, and kaempferol-3-O-α-L-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Although several compounds have been found in the extracts of T sinensis 15 and A camphorata , 17 the primary objective of this study was to demonstrate the synergistic contribution of the anticancer potential of T sinensis and A camphorata against HL-60 cells through an apoptotic pathway. Our results strongly suggested that the combined treatment of T sinensis and A camphorata has offered more beneficial effects on the suppression and treatment of leukemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several compounds have been found in the extracts of T sinensis 15 and A camphorata , 17 the primary objective of this study was to demonstrate the synergistic contribution of the anticancer potential of T sinensis and A camphorata against HL-60 cells through an apoptotic pathway. Our results strongly suggested that the combined treatment of T sinensis and A camphorata has offered more beneficial effects on the suppression and treatment of leukemia.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Sun et al established an efficient and reliable HPLC-DAD (high-performance liquid chromatography diode-array detector) method for the characterization of phytochemical compounds from the T sinensis leaf extracts and reported that rutinoside, quercetin-3-O-β-D-glucoside, quercetin-3-O-α-L-rhamnoside, and kaempferol-3-O-α-L-rhamnoside were the 4 reported major flavonol glycoside compounds from these leaf extracts. 15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roem., is a type of edible vegetable that is widely applied in South-East Asia as a type of traditional Chinese medicine (TCM) in clinical practice [16]. The most abundant ingredients in T. sinensis leaf (TSL) extracts include gallic acid (10%), rutin (0.5%), quercetin (0.42%), quercitrin (0.15%), kaempferol 3-O-b-D-glucoside (0.06%), methyl gallate (0.02%), ethyl gallate (0.002%), quercetin 3-O-b-D-glucoside (< 0.002%), and kaempferol (< 0.002%) [17]. TSL aqueous extracts have various biopharmacological activities, including antioxidant [18,19], antidiabetes [20], neuron degenerative disease-suppressing [21], anti-in ammation [22], antivirus [23], and anticancer [24,25] properties.…”
Section: Introductionmentioning
confidence: 99%
“…Chinese Toon (Toona sinensis), a tree with both medicinal and edible uses, contains rich chemical substances with functions such as antifungal, antiglycation, or anti-tumor activities. Flavonoid compounds, especially anthocyanin, have been identified as the major bioactive constituents in Toona [2][3][4] which are considered to be of the most beneficial plant-derived antioxidants and have led to increased efforts to analyze the genetic controls of the mechanism of flavonoids synthesis [5,6].…”
Section: Introductionmentioning
confidence: 99%